Politeness expressions in German textbooks: Cultural values representation and relevance in foreign language learning - Megawati, Sri; Mulyati, Retna Endah Sri; Novitasari, Rahma Kurnia; Zimmermann, Michaela (Diksi, 2025)
German textbooks typically emphasize grammatical and lexical aspects while paying less attention to pragmatic elements, especially politeness strategies that reflect native speakers’ cultural values. The study examined polite expression forms, functions, and the cultural value of German textbooks and analyzed their relevance to the development of intercultural competence. We used a qualitative research design based on the German textbook Netzwerk A1, A2, and B1, authored by Dengler et al. (2020) and published by Ernst Klett Sprachen GmbH as a data source. Data were collected through reading and recording techniques, then analyzed using pragmatic matching and distributional methods. The validity was checked through observation, triangulation, and peer review. The analysis revealed five main categories of politeness forms: (1) grammatical and lexical forms, (2) standard expressions of politeness, (3) modal particles, (4) formal pronouns Sie 'your', and (5) indirect questions. These forms consistently showed German cultural values such as social hierarchy, formality, and politeness norms. Given the results, we suggest that German textbooks should include more sociopragmatic elements to help students develop better cross-cultural communication skills.